Analisis Profil Muka Air Banjir Sungai Way Sikula Kota Ambon Menggunakan HEC – RAS - Rolobessy, Vivi Elfira; Warniyati, Warniyati; Sihombing, Tri Octaviani; Tutkey, Monica Rina (Jurnal Teknik Sipil, 2024)
The Way Sikula River is one of the rivers in Ambon City with a length of 22.55 km. The Way Sikula River is in the Way Sikula and Air Manis watersheds. In July 2022, there was a flood downstream of the river which resulted in paralyzed road access to Ambon City and West Leihitu District. In this regard, it is necessary to analyze the profile of the flood water level in the river which is expected to become a flood control plan in the future. Calculation of flood discharge in the Way Sikula River for return periods of 2, 5, 10, 25, and 50 years used the rational method using rainfall data from the BMKG Pattimura Ambon station and Gunung Nona Ambon Post Station in 2012 - 2021. The results of the flood discharge calculation for the 2012-2021 period. 2nd, 5th, 10th, 25th and 50th year respectively are 99,51 m3/s, 130,47 m3/s, 150,36 m3/s, 168,87 m3/s and 192,74 m3/s. Floodwater profile analysis using HEC-RAS ver. 5.0.7. From the simulation results it is known that the Way Sikula River began to overflow at the Q2 year flood discharge in all simulated cross sections with a flood overflow height at a 50 year flood discharge reaching 1,86 meters.